Nonconvulsive status epilepticus: Epilepsy Research Foundation Workshop Reports - Walker, Matthew; Cross, Helen; Smith, Shelagh; Young, Camilla; Aicardi, Jean; Appleton, Richard; Aylett, Sarah; Besag, Frank; Cock, Hannah; DeLorenzo, Robert; Drislane, Franck; Duncan, John; et al. (Epileptic disorders, 2005)
In April 2004, a group of physicians with an interest in nonconvulsive status epilepticus representing a spectrum of opinion met in Oxford, sponsored by the Epilepsy Research Foundation (a charitable organization), to discuss and debate the definition, diagnosis and treatment of nonconvulsive status epilepticus. We felt that such a meeting would be useful, as nonconvulsive status epilepticus is a subject that provokes strong reactions, perhaps largely due to the relative lack of evidence and the surfeit of opinion. The meeting was arranged such that there were formal talks followed by a discussion led by one of the attendees. We present here the extended abstracts of the main talks with the points raised by the discussants. Despite disagreements on certain issues there was much in the way of consensus. First, it was agreed that nonconvulsive status epilepticus is a term that covers a range of disparate conditions with varying prognoses and treatments. The agreed definition was thus suitably vague, «Nonconvulsive status epilepticus is a term used to denote a range of conditions in which electrographic seizure activity is prolonged and results in nonconvulsive clinical symptoms». Secondly, it was agreed that even within a specific condition ( e.g. complex partial status epilepticus), the prognosis and treatment depends upon the context in which the condition occurs ( e.g. in the critically ill, in coma, in the «walking wounded» and in people with prior epilepsy). Perhaps, most importantly it was agreed that we lacked good clinical data, and the challenge was to design good studies for a condition that is underrecognised and often difficult to diagnose.